2019
DOI: 10.1097/pr9.0000000000000722
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aging on hydromorphone-induced thermal antinociception in healthy female cats

Abstract: Introduction: This study aimed to evaluate the effects of aging on hydromorphone-induced thermal antinociception in cats. Methods: In a prospective, randomized, blinded, controlled design, 10 healthy female cats received each of the following treatments intramuscularly: hydromorphone (0.1 mg/kg) and 0.9% saline (0.05 mL/kg) with a 1-week washout between treatments at 6, 9, and 12 months of age. Skin temperature and thermal thresholds (TTs) were recorded before and up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In that study, hydromorphone provided a shorter duration and smaller magnitude of antinociception in the same cats at 6 months when compared with 9 and 12 months. These results suggest that 6-month-old kittens may require more frequent dosing of opioids than adults (Simon et al 2019).…”
Section: Indicationsmentioning
confidence: 82%
See 2 more Smart Citations
“…In that study, hydromorphone provided a shorter duration and smaller magnitude of antinociception in the same cats at 6 months when compared with 9 and 12 months. These results suggest that 6-month-old kittens may require more frequent dosing of opioids than adults (Simon et al 2019).…”
Section: Indicationsmentioning
confidence: 82%
“…Buprenorphine may be an alternative and associated with minimal respiratory depression. The duration and magnitude of thermal antinociception after hydromorphone administration in cats was shorter and lower, respectively, in cats aged 6 months compared to 9 and 12 months of age, respectively (Simon et al 2019). In each case, the clinical response to treatment should guide dosing.…”
Section: Opioidsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that age can influence thermal antinociception produced by opioids in cats. 88 Specifically, hydromorphone provided a shorter duration and smaller magnitude of antinociception in cats of 6 months of age than in the same individuals at 9 and 12 months of age. 88…”
Section: Treatment Of Pain – Analgesic Drugsmentioning
confidence: 86%
“…88 Specifically, hydromorphone provided a shorter duration and smaller magnitude of antinociception in cats of 6 months of age than in the same individuals at 9 and 12 months of age. 88…”
Section: Treatment Of Pain – Analgesic Drugsmentioning
confidence: 86%